2022
DOI: 10.1097/mao.0000000000003767
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors and Sudden Sensorineural Hearing Loss: A Case-Control Study

Abstract: ObjectiveTo investigate the role of cardiovascular risk factors (specifically hypertension [HTN], hyperlipidemia/dyslipidemia, diabetes mellitus I and II, and body mass index (BMI) on the development of sudden sensorineural hearing loss (SSNHL).Study DesignCase-control retrospective chart review.SettingA tertiary referral center.PatientsPatients aged 18 to 85 years who presented to the clinic over a 1-year span (September 17, 2020 to September 17, 2021) for evaluation of sudden sensorineural hearing loss.Main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Because this artery has no collateral circulation, once thrombosis or vasospasm occurs, it will lead to ear ischemia, hypoxia, microcirculation disturbance, further damage to the inner ear, and even irreversible deafness [ 21 ]. Clinical research showed that, vascular disease plays a very important role in SSNHL, and cochlear microcirculation disorder caused by vascular diseases is a common cause of SSNHL [ 22 , 23 ]. The results of this study showed that the levels of hemodynamic indexes in patients with SSNHL was significantly higher than that of healthy subjects, and the levels of hemodynamic indicators were gradually increased with the increased degree of hearing loss, which were significantly correlated with the degree of hearing loss in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because this artery has no collateral circulation, once thrombosis or vasospasm occurs, it will lead to ear ischemia, hypoxia, microcirculation disturbance, further damage to the inner ear, and even irreversible deafness [ 21 ]. Clinical research showed that, vascular disease plays a very important role in SSNHL, and cochlear microcirculation disorder caused by vascular diseases is a common cause of SSNHL [ 22 , 23 ]. The results of this study showed that the levels of hemodynamic indexes in patients with SSNHL was significantly higher than that of healthy subjects, and the levels of hemodynamic indicators were gradually increased with the increased degree of hearing loss, which were significantly correlated with the degree of hearing loss in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The maxillary sinus is primarily supplied with blood through branches of the maxillary artery, including the posterior lateral nasal artery, the infraorbital artery, and the posterior superior alveolar artery. The maxillary sinus and its mucosa are primarily innervated by the maxillary division of the trigeminal nerve [ 9 ]. The maxillary sinus is one of the frequently injured anatomical sites in midfacial fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cholesterol levels were higher in patients with SSNHL compared to controls, but no significant associations were found for smoking, HDL, LDL, triglyceride, or BMI [8]. In contrast, two studies found no association between SSNHL and comorbidities such as hypertension and diabetes, as well as smoking and drinking habits [9,10] or hyperlipidemia [10]. Alternatively, one study found higher levels of leukocytes, neutrophils, neutrophil-tolymphocyte ratio, and fibrinogen in patients with SSNHL [9].…”
Section: Comorbity Associationmentioning
confidence: 92%